2019
DOI: 10.1038/s41598-019-56466-z
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Reaction Monitoring reveals structure-specific ceramide alterations in the zebrafish

Abstract: Extensive characterisations of the zebrafish genome and proteome have established a foundation for the use of the zebrafish as a model organism; however, characterisation of the zebrafish lipidome has not been as comprehensive. In an effort to expand current knowledge of the zebrafish sphingolipidome, a Parallel Reaction Monitoring (PRM)-based liquid chromatography-mass spectrometry (LC-MS) method was developed to comprehensively quantify zebrafish ceramides. Comparison between zebrafish and a human cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 86 publications
(136 reference statements)
2
16
0
Order By: Relevance
“…(asah1a +68/+68 ; asah1b −20/−20 , Table 2, and Supplementary Table S1) zebrafish has also been generated using CRISPR-Cas9, and exhibited reduced size, ceramide accumulation, and early mortality [4 months-post-fertilization (mpf); Zhang X. et al, 2019]. No changes in size, ceramide content, or lifespan were observed in Asah1 single mutants, suggesting that Asah1a and Asah1b possess some functional redundancy (Zhang T. et al, 2019). More detailed phenotypic characterization of Asah1 mutants could shed further light on the functional impacts unique to each ohnologue.…”
Section: Hsp5mentioning
confidence: 99%
See 2 more Smart Citations
“…(asah1a +68/+68 ; asah1b −20/−20 , Table 2, and Supplementary Table S1) zebrafish has also been generated using CRISPR-Cas9, and exhibited reduced size, ceramide accumulation, and early mortality [4 months-post-fertilization (mpf); Zhang X. et al, 2019]. No changes in size, ceramide content, or lifespan were observed in Asah1 single mutants, suggesting that Asah1a and Asah1b possess some functional redundancy (Zhang T. et al, 2019). More detailed phenotypic characterization of Asah1 mutants could shed further light on the functional impacts unique to each ohnologue.…”
Section: Hsp5mentioning
confidence: 99%
“…Of the 23 LSD-associated human genes with zebrafish models, six (26%) have more than one orthologue in the zebrafish ( Table 2 and Supplementary Table S1). For Asah1 (Farber lipogranulomatosis) and Mcoln1 (mucolipidosis IV), where isogenic single and double mutants are both available (Li et al, 2017;Zhang T. et al, 2019), severe pathologies were associated only with the double mutant, suggesting that at least a portion of ohnologues share similar functions. Consequently, TGD adds additional complexity to the zebrafish genome, and necessitates the generation of double mutants in instances of functional redundancy.…”
Section: Finetuning Crispr-cas9 Mutagenesis In the Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…PRM (also referred to as HR MRM or MRM HR ) can achieve selection of interested precursor ions in the quadrupole and detection of characteristic fragments generated in the HRMS including Orbitrap and TOF, which has been widely used in the field of proteomics for large-scale quantification of peptides [ [80] , [81] , [82] , [83] ]. Recently, several PRM-based targeted lipidomics platforms have been applied for lipid discovery and quantification in human serum [ 84 ], zebrafish [ 85 ], barley root [ 86 ], yeast [ 87 ] and enterococcus faecalis [ 88 ]. For instance, Yu et al.…”
Section: Advances In Analytical Strategies For Mass Spectrometry-basementioning
confidence: 99%
“…A first zebrafish knockdown model showed a loss of motor neuron axonal branching [ 184 ]. A more recent study designed a CRISPR/Cas9 knockout for both orthologues asah1a and asah1b , successfully mimicking the characteristics of Farber disease [ 185 ]. Using parallel reaction monitoring (PRM)-based liquid chromatography–mass spectrometry (LC–MS) method for ceramide analysis, it was shown that a double knockout is required to significantly increase ceramide content in the zebrafish brain, as either asah1a or asah1b was sufficient to maintain physiological levels.…”
Section: Lysosomal Storage Disordersmentioning
confidence: 99%